2020
DOI: 10.1016/j.curtheres.2020.100610
|View full text |Cite
|
Sign up to set email alerts
|

Association of Monoamine Oxidase A with Tumor Burden and Castration Resistance in Prostate Cancer

Abstract: Background Metastatic burden and aggressive behavior determine severity stratification and guide treatment decisions in prostate cancer (PCa). Monoamine oxidase A (MAOA) may promote tumor burden and drug/castration resistance in PCa. A positive association will pave the way for MAOA inhibitors such as moclobemide for PCa therapy. Objective To analyze MAOA in peripheral blood mononuclear cells qualitatively and p38, c-Jun N-terminal kinases, nuclear factor kappa B, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…MAOA is highly expressed in PCa [ 87 ], and its degree of expression varies with disease development [ 88 ]. Previous results demonstrated that MAOA was associated with PCa progression and played key roles during almost every stage of PCa development, including castrate-resistant PCa, neuroendocrine PCa, metastasis, drug resistance, stemness, and perineural invasion.…”
Section: Prospects and Expectationsmentioning
confidence: 99%
“…MAOA is highly expressed in PCa [ 87 ], and its degree of expression varies with disease development [ 88 ]. Previous results demonstrated that MAOA was associated with PCa progression and played key roles during almost every stage of PCa development, including castrate-resistant PCa, neuroendocrine PCa, metastasis, drug resistance, stemness, and perineural invasion.…”
Section: Prospects and Expectationsmentioning
confidence: 99%
“…MAOA induces YAP1 through downstream ROS/Twist1-dependent activation of Shh/Gli signaling for direct Gli1/2 interaction with a Gli-binding site in YAP1 promoter ( 31 ). Of note, MAOA expression is elevated and associated with AR activity in CRPC clinical specimens ( 31 , 32 ). Importantly, knocking down MAOA expression impeded tumor growth of both androgen-dependent LNCaP cells and castration-resistant C4-2B ENZR cells (a LNCaP-derived CRPC subline with acquired resistance to the antiandrogen drug enzalutamide) ( 31 ), indicating that MAOA is a valid target for AR-positive PC cells regardless of cellular reliance on androgens.…”
Section: Maoa Confers Castration Resistance In Pcmentioning
confidence: 99%
“…There are several explanations for the antiproliferative effects of MAO inhibitors in prostate cancer patients. A relationship between higher MAO levels and prostate-specific antigen (PSA), as well as the degree of severity of tumor progression, has been empirically demonstrated (Meenu et al, 2020). One important finding is based on the effect of MAO-A on epithelial-to-mesenchymal transition mediated signaling pathways.…”
Section: Dear Editormentioning
confidence: 99%